Human Rights and Human Nature
VI, 274 p.
Keywords: This book explores both the possibilities and limits of arguments from human nature in the context of human rights. Can the concept of human nature provide a basis for understanding fundamental rights? Is it plausible to justify the claim to universal validity of human rights by reference to human nature? Or does the idea of human rights in its modern, post-1945 manifestation go, in essence, beyond human nature? The essays in this volume introduce naturalistic positions and their concomitant critiques. They address the role that human nature both actually does and potentially may play in forming a foundation for and acting as an exemplification of fundamental rights. Beyond that, they give attention to the challenges caused by Life Sciences. Human nature itself is subject to transformation and transgression in an unprecedented manner. The essays reflect on issues such as reproduction, species manipulation, corporeal autonomy, and enhancement. Contributors are jurists, philosophers, and political scientists from Germany, Switzerland, Turkey, Poland, and Japan.